Star-shaped D-π-A oligothiophenes with a tris(2-methoxyphenyl)amine core and alkyldicyanovinyl groups: synthesis and physical and photovoltaic properties - Luponosov, Yuriy N.; Min, Jie; Solodukhin, Alexander N.; Bakirov, Artem V.; Dmitryakov, Petr V.; Shcherbina, Maxim A.; Peregudova, Svetlana M.; Cherkaev, Georgiy V.; Chvalun, Sergei N.; Brabec, Christoph; Ponomarenko, Sergei A. (Journal of Materials Chemistry C, 2016)
Synthesis of a series of star-shaped oligomers having a novel electron donating tris(2-methoxyphenyl)amine (m-TPA) core, which is linked through a bithiophene or terthiophene extgreekp-bridge with electron-deficient alkyldicyanovinyl (alkyl-DCV) groups, is described. A comprehensive study of the oligomers revealed significant dependence of their physical properties, including absorption, molecular frontier energy levels, crystal packing, and melting and glass transition temperatures, upon the chemical structure. A comparison of their photophysical properties to the nearest analog having the common dicyanovinyl (DCV) groups demonstrated a number of benefits to use alkyl-DCV units for the design of donor–acceptor small molecules: higher solubility, increased electrochemical stability, better photovoltaic performance, and possibility to control the relative physical and photovoltaic properties by a simple adjustment of alkyl and extgreekp-bridge lengths. Modification of the well-known triphenylamine (TPA) core in the star-shaped oligomers by methoxy groups increases not only solubility, but also crystallinity of the oligomers, whereas their photovoltaic performance stays on a similar level as their analogs with a TPA core. The study demonstrates that these design strategies represent interesting and simple tools for the effective modulation of properties of star-shaped molecules.
EAM Import::2019-03-13
Keywords: Engineering controlled terms: Crystal structure; Glass transition; Molecules; Oligomers; Solubility Design strategies; Electrochemical stabilities; Electron-deficient; Electron-donating; Photophysical properties; Photovoltaic performance; Photovoltaic property; Star-shaped molecules Engineering main heading: Stars